2015
DOI: 10.11604/pamj.2015.20.355.4714
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of medical students towards healthcare devolution: an online cross-sectional study

Abstract: IntroductionThere have been worries concerning the preparedness and capacity of the counties to take over health care services. As the current medical students are going into this new system, we sought their opinions on the issue of devolution. The objective is to assess beliefs and attitudes of medical students towards devolution of healthcare services.MethodsA cross sectional survey was conducted at University of Nairobi medical school during the period of February-May 2014. Though a calculated random sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…11 Furthermore, a research study reviewed that students have less understanding about the CAM use and it's side effects that shows students (34%) are in quandary regarding CAM which is a kind of similar to our study 41.7% out of total respondents are found in dilemma regarding CAM Practices. 23 In a study done, 3.2% agreed in including CAM in health science undergraduate curriculum while about 85% students agreed in our study. 24 In another research study, it was found that 76.3% preferred CAM alongside modern medicine which resembles to that our study (84.1%).…”
Section: Discussionmentioning
confidence: 46%
“…11 Furthermore, a research study reviewed that students have less understanding about the CAM use and it's side effects that shows students (34%) are in quandary regarding CAM which is a kind of similar to our study 41.7% out of total respondents are found in dilemma regarding CAM Practices. 23 In a study done, 3.2% agreed in including CAM in health science undergraduate curriculum while about 85% students agreed in our study. 24 In another research study, it was found that 76.3% preferred CAM alongside modern medicine which resembles to that our study (84.1%).…”
Section: Discussionmentioning
confidence: 46%
“…Kagendo (2013) observed that many students go home every day because they are feeling unwell or even because they have bruised themselves in school. Consequently, learners should be protected and given necessary medical attention while in school for learning to thrive well (Nyongesa, et al, 2015). Since school health practices by the principal affect students' retention rate in schools, this study was done to investigate the relationship between learners' health and the retention of students in Public Secondary Schools in Kisii County, Kenya.…”
Section: Editon Consortium Journal Of Curriculum and Educational Studies (Ecjces)mentioning
confidence: 99%
“…In addition, Mabonga (2017) observed that in the last two decades, health sector devolution policies have been implemented on a broad scale throughout the developing world, usually as part of a broader process of political, economic, and technical reform. Devolution of health services is widely practiced throughout the world especially in the developing countries to ensure improvement in the performance of the health system, increase population access to service and the efficiency of the delivered services (Noory, 2016;Muchomba & Karanja, 2015). The devolution of health system structure and management has been and continues to be a key issue for many countries in the achievement of health for all, and development of primary health care (Mwatsuma & Nyamu, 2014).…”
Section: Introductionmentioning
confidence: 99%